Tourism Policy as a Poverty Transformation Instrument in Advancing Localized SDGs Implementation - Sitti Hairani Idrus; La Ode Muhammad Golok Jaya (PT FORMOSA CENDEKIA GLOBAL, 2026)
Tourism is recognized as a strategic sector in achieving the SDGs, especially poverty alleviation and inclusive economic growth. However, the effectiveness of tourism policies as an instrument of poverty transformation at the local level still varies. This study aims to analyze the role of government policies in the tourism sector in transforming poverty within the framework of localized SDGs implementation. Using a qualitative policy analysis approach through the study of regulatory documents and regional planning, the results of the study show that tourism policies are effective when integrating institutional alignment, community-based community empowerment, and strengthening local economic value chains. However, policy fragmentation and limited regional capacity are the main challenges. This study concludes that tourism policy can be an instrument for sustainable poverty transformation if it is designed in the governance of the SDGs that emphasizes fair distribution, participation, and strengthening the local economy.